Gender violence in failed and democratic states : besieging perverse masculinities - Rodríguez, Ileana (Comparative feminist studies series., 2016)
This book presents original research of violence against women in both achieved and failed states (i.e. Austria, the United States, and Nicaragua) from both a political and psychological perspective. Ileana Rodriguez presents various cases studies that showcase the hard data provided by articles on gender violence (incest, rape, feminicide) in the media, with advanced feminist theories leaning on Freud and Lacan, and with literary fiction that speaks of masculine desire.